Metodología para la planeación, control y gestión de la producción y las operaciones de Kumara SAS. (2021)
This research article will analyse a methodology for the planning, control and management of production and operations of Kumara SAS, a Mipyme in the city of Bogotá D.C., dedicated to the production and marketing of frozen vegan products. The first step for the construction of the methodology focuses on the identification of cause-effect that affect the planning system within the production area of the MiPyme under study; the validation of the causes was carried out through secondary sources and the application of interviews to the management of the company.